Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India - Zacharias, Merry; Rajan, Priyadarsanan Dharma (Zootaxa, 2004)
Discothyrea sringerensis sp. nov. is described and is the first record of this genus from South India. The other known species of Discothyrea are scattered within the tropics and the temperate zones of the world. Based on workers, D. sringerensis is most similar to the species described from Malaysia and Australia characterised by 10-segmented antennae.